PERLINDUNGAN HUKUM BAGI KREDITUR AKIBAT WANPRESTASI DEBITUR PADA PEMBIAYAAN BERBASIS PEER TO PEER LANDING SYARIAH PERSPEKTIF POJK NO. 22 TAHUN 2023 - Fauziah Lubis; Nazwa Febrianti (CV Rewang Rencang, 2024)
This research aims to analyze and find out how legal protection for creditors. Fintech Peer to Peer Landing Syariah raises a legal problem such as bad credit or default by the debtor so that it has an impact on losses to creditors. This research uses normative legal research methods. Legal protection for online loan users is a major issue in the development of peer to peer lending. Consumer protection regulations are regulated in various rules, one of which is the Financial Services Authority Regulation Number 22 of 2023. In this case, the lender as a creditor has the right to collect and can cooperate with other parties to collect credit or financing from debtors who default. And the form of responsibility of the organizer should be able to provide protection funds in the form of credit or financing insurance. In the view of Islam, insurance is allowed as long as it is in accordance with Islamic principles, sharia insurance uses a tabarru 'contract which has the aim of helping. The legal basis of Islamic insurance is Al-Maidah verse 2, An-Nisa verse 9 and the narration of HR Muslim Abu Hurairah, Fatwa No. 21/DSN-MUI/X/2001, Fatwa No. 51/DSN-MUI/III/2006, Fatwa No. 52/DSN-MUI/III/2006, and Minister of Finance Regulation No. 18/PMK.010/2010.